2006
DOI: 10.1208/pt070376
|View full text |Cite
|
Sign up to set email alerts
|

Development of tetracycline-serratiopeptidase-containing periodontal gel: Formulation and preliminary clinical study

Abstract: The purpose of this research was to reduce the polymer concentration and to obtain reasonable viscosity at a lower concentration of pluronic by the addition of a viscosity modifier. A 20% wt/wt pluronic gel was prepared on a weight basis using the cold method. The effect of the amount of tetracycline and Aerosil on gel properties was studied. The gel was evaluated using different parameters: polarizing microscopy, gelation, gel melting, bioadhesivity, viscosity, drug release, and stability of enzyme. An in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 37 publications
(38 reference statements)
0
52
0
3
Order By: Relevance
“…Thus, the tetracycline gel formulation along with with scaling root and planning was effective in reducing gingival inflammation, bleeding on probing, pocket depth and increasing clinical attachment. 8 In summary, our result suggest that tetracycline gel with 0,5% concentration is effective in inhibiting the growth of subgingival plaque bacteria. …”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Thus, the tetracycline gel formulation along with with scaling root and planning was effective in reducing gingival inflammation, bleeding on probing, pocket depth and increasing clinical attachment. 8 In summary, our result suggest that tetracycline gel with 0,5% concentration is effective in inhibiting the growth of subgingival plaque bacteria. …”
Section: Discussionmentioning
confidence: 55%
“…13 By applicating tetracycline as gel, it can be absorbed into the gingival connective tissue and penetrate the root surface, therefore increasing the antibacterial capacity towards periodontopathogenic bacteria. 8 In addition, Tetracycline also inhibits the activity of matrix metalloproteinase produced by PMN (MMP-8 and MMP-9) by binding Ca 2+ and Zn 2+ which is located at its active side. So it inhibits the resorption of alveolar bones and collagen degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Periodontal gel formulations containing tetracyclineserratiopeptidase has shown better results along with non surgical therapy. 21 In summary, the studies reported that tetracycline fibers used as a monotherapy without non surgical therapy were effective at decreasing probing depths, in gaining clinical attachment and reducing bacterial load.…”
Section: Dental Applications Of Pharmacotherapeutic Agents Used In Lddmentioning
confidence: 97%
“…In a 6-month multi-centre evaluation of adjunctive tetracycline fibre therapy by Newman et al 1994, showed that fibre therapy significantly enhanced the effectiveness of scaling and root planing in the management of localized recurrent periodontitis sites, in patients receiving regular supportive periodontal therapy 7 . A Tetracycline-SerratiopeptidaseContaining Periodontal Gel made by Maheshwari et al observed that Formulation has shown statistically significant results along with scaling and root planing 8 . Singh et al 2009 reported that there is no statically significant difference in the results achieved with local tetracycline hydrochloride or local metronidazole as adjuncts to mechanotherapy 9 .…”
mentioning
confidence: 99%